Plan de integración de los sistemas de gestión de la inocuidad y de ambiental en una pyme del sector de alimentos (2017)
In this degree project, the planning stage of an integrated management system based on the ISO 22000: 2005 and ISO 14001: 2015 standards of an SME of the food sector is presented, the case study company is a family micro-enterprise of meat sausages with More than 20 years of experience, located in the city of Bogotá DC Currently, it does not have a certification in quality standards that will generate a competitive advantage in the market and venture into large chains nationwide.